Patient characteristics do not predict the individual response to antihypertensive medication: a cross-over trial. (31st August 2017) - van der Wel, Mark C; Biermans, Marion; Akkermans, Reinier; Lenders, Jacques WM; van Weel, Chris; Deinum, Jaap
Abstract: Background: International guidelines on hypertension management do not agree on whether patient characteristics can be used for the first choice of treatment of uncomplicated essential hypertension. Objective: We wanted to identify predictive patient characteristics to the response of two different classes of antihypertensive drugs in patients with newly diagnosed hypertension in primary care. Methods: We conducted a prospective, open label, blinded endpoint cross-over trial in 120 patients with a new diagnosis of hypertension from 10 family practices. Patients received 4 weeks of 12.5 mgr hydrochlorothiazide once daily and 4 weeks of 80 mgr valsartan once daily, each followed by a 4-week washout. The sequence of drugs was randomized. Age, sex and menopausal state were recorded at run in and 24 h ambulatory blood pressure, office blood pressure, plasma renin concentration, NT-proBNP, potassium, estimated glomerular filtration rate, urinary albumin, body mass index and waist circumference at each regimen change. The difference in systolic blood pressure response between both study drugs, calculated from mean daytime ambulatory blood pressures, was the main outcome measure. Results: Ninety-eight patients (52% female; median age 53 years) were eligible for per-protocol-analysis. None of the studied variables were predictive for the difference in systolic blood pressure response. Individual systolic blood pressure responses ranged from an increase by 18 mmHg to a decrease of 39 mmHg. Conclusion: In a relevant group of primary care patients with newly diagnosed hypertension, we were unable to detect predictors of treatment response. This study rather supports the United States and European guidelines than the United Kingdom and Dutch guidelines on hypertension.